2000
DOI: 10.1046/j.1365-2249.2000.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Mouse strain and conditioning regimen determine survival and function of human leucocytes in immunodeficient mice

Abstract: SUMMARYThe innate immune system of severe combined immunodeficient (SCID) mice represents an important barrier to the successful engraftment of human cells. Different genetic and pharmacological strategies improve the graft survival. Non-obese diabetic (NOD)-SCID mice are better hosts for reconstitution with human peripheral blood leucocytes (Hu-PBL) because of their reduced natural killer cell and macrophage activity next to defective T and B cell functions. We investigated effects of TM-b1, a rat monoclonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 24 publications
3
51
0
Order By: Relevance
“…In addition to T-and B-cell deficiency, NOD/SCID mice have functional defects of macrophages and natural killer cells (31)(32)(33)(34) and high rates of human lymphocyte engraftment (34), providing a tool for studying human islet allograft rejection and the effect of immunomodulatory agents (25,28,35,36). The rate of T-cell engraftment observed in our study was similar to that described by other authors studying the same strain of mice (34).…”
Section: Discussionsupporting
confidence: 85%
“…In addition to T-and B-cell deficiency, NOD/SCID mice have functional defects of macrophages and natural killer cells (31)(32)(33)(34) and high rates of human lymphocyte engraftment (34), providing a tool for studying human islet allograft rejection and the effect of immunomodulatory agents (25,28,35,36). The rate of T-cell engraftment observed in our study was similar to that described by other authors studying the same strain of mice (34).…”
Section: Discussionsupporting
confidence: 85%
“…[45,[51][52][53][54] The mechanism/s by which pre-transplant irradiation of NOD/SCID-β2m null recipients increases the incidence of lethal X-GVHD induced by huT cells remains unknown. One possibility is that TBI provides additional immunosuppression, thereby permitting increased huT cell engraftment and subsequent development of lethal X-GVHD [23]. Consistent with this hypothesis, we found significantly increased huT cell engraftment in the peripheral blood of NOD/SCID-β2m null mice after increasing the TBI dose from 250 cGy to 300 cGy and decreasing the time between irradiation and huT cell injection from 24 h to <6 h. A second possibility is that the pre-transplant irradiation prompts massive cytokine induction, also known as the "cytokine storm", which promotes huT cell engraftment, activation and development of lethal X-GVHD [49].…”
Section: Discussionmentioning
confidence: 99%
“…Initial experiments using SCID mice, which lack functional T and B-cells, demonstrated that anywhere from 1% to 20% of unconditioned SCID mice could develop xenogeneic GVHD (X-GVHD) following intraperitoneal (i.p.) injection of extremely high numbers (50-100 × 10 6 ) of human peripheral blood mononuclear cells (huPBMCs) [14,[17][18][19][20][21][22][23]. Nonobese diabetic (NOD)/SCID mice exhibit reduced NK activity, macrophage function and serum hemolytic complement activity in addition to the deficit in mature T and B cells [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations